Andre the Giant : life and legend - Brown, Box (First Second, an imprint of Roaring Brook Press, 2014)
Drawing from historical records about Andre's life as well as a wealth of anecdotes from his colleagues in the wrestling world, including Hulk Hogan, and his film co-stars (Billy Crystal, Robin Wright, Mandy Patinkin, etc), Brown has created in Andre the Giant, the first substantive biography of one of the twentieth century's most recognizable figures.